San Francisco March for Peace in Central America and Equality in South Africa - Watkins, Howard::::::::: (1987)
Christine Watkins, Robin Watkins, Howard Watkins and Adam Watkins with protest signs in front of Fresno banner "Fresno Wants Peace in Central America + Equality in South Africa"